Review—CNT-Based Water Purification and Treatment Strategies - Islam, Mohammed Saydul; Rockshat, Md.; Jahan, Israt; Islam, Jahidul; Zabed, Hossain M.; Khandaker, Mayeen Uddin *; Rahman, Ismail M. M.; Chowdhury, Faisal Islam (The Electrochemical Society, 2023)
Over the recent century, the scarcity of pure drinking water has been increasing worldwide, and due to the overwhelming rise in demand the situation could be exacerbated to a greater extent in the upcoming days. To remit this global issue, several technologies for purifying water have been developed which are limited by certain factors. Therefore, research interests in nanomaterials-based water purification technologies are growing to tackle water scarcity. Among the various proposed methods and nanomaterials, CNTs and functionalized CNTs are superior to water purification and treatment processes due to configurable properties such as high surface area, high reactivity, lower cost, and less adverse effects on the environment. This review will introduce most of the CNTs and functionalized CNTs-based water purification and treatment technologies and the challenges associated with these applications. The comparative studies among these methods will also be discussed which will help the researchers to bring novel CNTs-based efficient technologies in the near future for a sustainable world.